EFFECT OF EDUCATIONAL INTERVENTIONS ON HIV/AIDS KNOWLEDGE, SEXUAL BEHAVIOR AND PERCEIVED SELF-EFFICACY AMONG FEMALE APPRENTICES IN BENIN-CITY, NIGERIA. (2013)
Globally female youths are disproportionately affected by HIV. They tend to participate in more risky sexual activities especially those in apprenticeship. In Nigeria, interventions addressing the reproductive health needs of female youths are scarce. This study was carried out to compare the relative effectiveness of three interventions: peer education, education by instructors and a combination of the two on HIV prevention and safer sex among female apprentices in Benin-City. Benin-City was purposively selected as study site. The quasi-experimental study involved systematically selected 804 female apprentices drawn from 200 shops (120 tailoring and 80 hairdressing saloons). The shops were assigned to three intervention groups and a control. The apprentices’ baseline information was obtained using a semi-structured questionnaire consisting of 21-point HIV knowledge, 26-point risky sexual activities and 21-point perceived self–efficacy scales. The intervention groups were shops whose apprentices received Peer Education alone (PE), Education by Apprentices’ Instructors alone (EAI); and combination of both (PE+EAI) relating to HIV prevention. The interventions consisted of training of randomly selected 100 apprentices as peer educators on HIV prevention and counselling. They administered the intervention on the apprentices in their shops for six months, completed in March 2010; the control received no intervention. Post-intervention evaluation was conducted at intervals of three and six months. The number of participants at baseline, three and six months were 201, 199 and 200 for PE; 200, 200 and 200 for EAI; 201, 198 and 200 for PE+EAI; and 202, 198 and 198 for the control group. Data were analysed using descriptive statistics, Chi square, t-test and ANOVA at p=0.05. Mean ages of respondents in PE, EAI, PE+EAI and control were 21.9 3.8, 21.5 2.8, 21.8 2.9 and 22.1 3.6 years respectively. Majority were singles: PE (86.6%), EAI (96.0%), PE+EAI (82.6%) and control (75.7%). Apprentices who completed Senior Secondary School education were PE (38.8%), EAI (58.0%), PE+AEI (27.4%) and control (48.0%). Mean knowledge scores at baseline were 10.8±3.6 (PE); 14.0±2.3 (EAI); 9.6±2.9 (PE+EAI) and 10.2±3.2 (control); these increased to 16.3±1.2, 15.8±1.9, 16.8±0.8 and 15.5±1.5 at three months; to 16.5±1.2; 17.1±0.7; 17.0±0.5 and 14.3±1.5 at six months for PE, EAI, PE+EAI and control respectively; there was significant increase in knowledge among intervention groups. At six months, there were significant reductions in proportions of respondents who had >1 sexual partner from 16.4% to 0.0% (PE), 3.0% to 0.0% (PE+EAI), 22.9% to 4.0% (control) but in EAI it increased from 0.0% to 2.1%. Comparing baseline with post-intervention data, respondents who reported condom use increased from 77.5% to 95.5% (PE), 82.0% to 85.6% (EAI), 49.0% to 76.8% (PE+EAI) and 58% to 60.3% (control) with significant differences only in the experimental groups. Difference between baseline and post-intervention mean score for perceived self-efficacy increased significantly in PE (from 12.1±2.9 to 16.6±3.7) and PE+EAI (10.4±5.0 to 13.6±2.8), but marginal increase in EAI (11.6±3.5 to 13.5±1.7) and control (11.2±2.9 to12.8±3.4). Combination of education by peers and apprentices’ instructors yielded more positive impact in knowledge and use of condom than single approach. It is recommended for use among female apprentices and policies should be formulated to support more interventions among this population.